Blunted Suppression of Acyl-Ghrelin in Response to Fructose Ingestion in Obese Adolescents: the Role of Insulin Resistance - Van Name, Michelle (Obesity (Silver Spring), 2015)
OBJECTIVE: Fructose consumption has risen alongside obesity and diabetes. Gut hormones involved in hunger and satiety (ghrelin and PYY) may respond differently to fructose compared to glucose ingestion. We evaluated the effects of glucose and fructose ingestion on ghrelin and PYY in lean and obese adolescents with differing insulin sensitivity. METHODS: Adolescents were divided into lean (n=14), obese insulin sensitive (n=12) (OIS), and obese insulin resistant (n=15) (OIR). In a double-blind, cross-over design, subjects drank 75g of glucose or fructose in random order, serum was obtained every 10 minutes for 60 minutes. RESULTS: Baseline acyl-ghrelin was highest in lean and lowest in OIR (p=0.02). After glucose ingestion acyl-ghrelin decreased similarly in lean and OIS, but appeared lower in OIR (vs lean p=0.03). Suppression differences were more pronounced after fructose (lean vs. OIS p=0.008, lean vs. OIR p<0.001). OIS became significantly hungrier after fructose (p=0.015). PYY was not significantly different at baseline, varied minimally after glucose, and rose after fructose. CONCLUSION: Compared to lean, OIS adolescents have impaired acyl-ghrelin responses to fructose but not glucose, whereas OIR adolescents have blunted responses to both. Diminished suppression of acyl-ghrelin in childhood obesity, particularly if accompanied by insulin resistance, may promote hunger and overeating.